A GC–MS-based untargeted metabolomics approach for comprehensive metabolic profiling of mycophenolate mofetil-induced toxicity in mice - Zhao, Tongfeng; Zhao, Yaxin; Chen, Haotian; Sun, Wenxue; Guan, Yun (Frontiers in Molecular Biosciences, 2024)
Background: Mycophenolate mofetil (MMF), the morpholinoethyl ester of mycophenolic acid, is widely used for maintenance immunosuppression in transplantation. The gastrointestinal toxicity of MMF has been widely uncovered. However, the comprehensive metabolic analysis of MMF-induced toxicity is lacking. This study is aimed to ascertain the metabolic changes after MMF administration in mice.Methods: A total of 700 mg MMF was dissolved in 7 mL dimethyl sulfoxide (DMSO), and then 0.5mL of mixture was diluted with 4.5 mL of saline (100mg/kg). Mice in the treatment group (n = 9) were given MMF (0.1mL/10g) each day via intraperitoneal injection lasting for 12 weeks, while those in the control group (n = 9) received the same amount of blank solvent (DMSO: saline = 1:9). Gas chromatography-mass spectrometry was utilized to identify the metabolic profiling in serum samples and multiple organ tissues of mice.The potential metabolites were identified using orthogonal partial least squares discrimination analysis. Meanwhile, we used the MetaboAnalyst 5.0 (http://www.metaboanalyst.ca) and Kyoto Encyclopedia of Genes and Genomes database (http://www.kegg.jp) to depict the metabolic pathways.The percentages of lymphocytes in spleens were assessed by multiparameter flow cytometry analysis.Results: Compared to the control group, we observed that MMF treatment induced differential expression of metabolites in the intestine, hippocampus, lung, liver, kidney, heart, serum, and cortex tissues. Subsequently, we demonstrated that multiple amino acids metabolism, aminoacyl-tRNA biosynthesis, energy metabolism and fatty acids biosynthesis were disrupted following MMF treatment. Additionally, MMF challenge dramatically increased CD4 + T cell percentages but had no significant influences on other types of lymphocytes.MMF can affect the metabolism in various organs and serum in mice. These data may provide preliminary judgement for MMF-induced toxicity and understand the metabolic mechanism of MMF more comprehensively.